Social Criticism In Wladyslaw Szpilman’s Novel The Pianist - Ririn Risnayanti Minanga; Dahlia D. Moelier; Asyrafunnisa Asyrafunnisa (Humaniora: Journal of Linguistics, Literature, and Education, 2022)
This study aimed to discover and explained the types of social criticism in Wladyslaw Szpilman’s novel entitled ‘’The Pianist’’ and this study was hope to be utilized by further researcher. The data sources used in this study was the novel ‘’The Pianist’’. In analyzing the data, the writer used descriptive qualitative research method through sociological approach. Data were obtained by using the techniques of reading, noting and analyzing. While in classifying the data, the writer used Marx’s theory of nine concepts of social criticism and used Alan Swingewood’s theory sociological of literature. The writer found that some the social critism such as: social criticism of political problems, social criticism of economic problems, social criticism of educational problems, cultural problems, social criticism of moral issues, social criticism of family problems, social criticism of religious problems and social criticism of technology problems. The most dominant data were social criticism of moral issues.